A grounded theory study on importance of English language in Indian schools - Vincent Roy, Joel (2018)
English is the most sought after language in the education sector in India. Parents prefer to send their children to English medium schools rather than the regional medium schools. English is very important to find jobs, study abroad, etc. The factors affecting the students to choose English medium schools were studied. Factors like Social pressure, jobs, parents and study abroad were identified.